Documentación primaria y crónicas históricas: efectos de las circunstancias en la versión de los hechos - Suñe Blanco, Beatriz (Revista Española de Antropología Americana, 2003)
This paper presents some of drawings made by the Guatemalan artist Antonio Tejada Fonseca when working for the Carnegie Institution archaeological missions in the Past Century Forties. More specifically, we show and comment here the images of a number of ceramics recovered from the excavations performed by Alfred Kidder and Edwin Shook at the finca El Paraíso, Quetzaltenango (Guatemala).